Enhancement of aromatics from catalytic pyrolysis of yellow poplar: Role of hydrogen and methane decomposition - Moogi, Surendar; Jae, Jungho; Kannapu, Hari Prasad Reddy; Ahmed, Ashfaq; Park, Eun Duck; Park, Young Kwon (Bioresource Technology, 2020)
The present study examined the effects of the pyrolysis environment on BTEX (benzene, toluene, ethylbenzene, and xylenes) production in the catalytic upgrading of yellow poplar pyrolysis vapors. Three different gas environments, N2, CH4, and pre-decomposed CH4 stream (10 wt%-Ni/5 wt%-La2O3-5 wt% CeO2-Al2O3), which is a mixture of H2 (55.62%) and CH4, were studied using two types of zeolite catalysts, HZSM-5, and 1 wt% Ga/HZSM-5. The BTEX yields were enhanced linearly in the order N2 < CH4 < CH4 ex-situ decomposition. The highest BTEX yield of 9.58 wt% was obtained under the CH4 ex-situ decomposition environment over 1 wt% Ga/HZSM-5. The methane and hydrocarbons derived from biomass were activated on highly dispersed (GaO)+ sites and transformed smoothly to BTEX by aromatization on the BrØnsted acid sites of Ga/HZSM-5. The hydrogen produced from methane decomposition also assisted in aromatics production through the hydrodeoxygenation of methoxyphenols, guaiacols and catechols.
Keywords: Benzene , toluene , ethylbenzene , and xylenes; Catalytic pyrolysis; Catalytic upgrading; Gas environment; Hydrodeoxygenation; Methane decomposition; Methoxyphenols; Zeolite catalyst; Biomass; Catalysis; Hot Temperature; Hydrogen; Liriodendron; Methane; Pyrolysis; Aromatics; Catalytic co-pyrolysis; CH4 decomposition; Ga/HZSM-5; Yellow poplar